Pengaruh Manajemen Waktu Dan Motivasi Mahasiswa Yang Kuliah Sambil Bekerja Terhadap Prestasi Akademik Mahasiswa Pada Prodi Manajemen Universitas Terbuka Semarang - Syahrinullah, Syahrinullah; Fitriana (Pascasarjana Universitas Muhammadiyah Mamuju, 2025)
In Indonesia, students who work and study at the same time is not a new thing. In fact, the goal of students should be to carry out all processes in higher education, namely to complete lectures on time, get a good achievement index and achieve learning goals in developing their mindset. This study aims to find out and analyze the influence of time management, student motivation on student academic achievement in studying while working. The method of this research is qualitative descriptive. This research was conducted at SMPS Plus Latansa (Boarding School) Demak, which is a place for face-to-face tutorials for UT Pokjar Demak students. The source of data for this research comes from primary data from the results of questionnaires and interviews. Secondary data from literature studies, the internet and the results of previous research. The sample of this research is 34 management students of UT Pokjar Demak Management Study Program Semester 8. The results of this study show that the students of the UT Pokjar Demak management study program in semester 8 are quite good, namely students can manage their time and determine their priorities. Meanwhile, student motivation in learning is quite good in terms of having the desire to learn and having ideals and hopes so that the average academic achievement of students is also quite good, which is between 2.75-3.50